Method development for fatigue lifeprediction in welded gearset joints undertorsional loading - Olsson, Emma (Luleå tekniska universitet, Institutionen för teknikvetenskap och matematik, 2021)
This report presents the degree project for a master's degree in Mechanical Engineeringat Luleå University of Technology performed by Emma Olsson at GKN ePowertrain in Köping. The aim of the thesis was to develop a calculation method to evaluate fatigue ina weld due to torsion. During the degree project, two di erent calculation methods weredeveloped - An analytical method and a numerical method. The analytical method is based on a calculation method already used at GKN for calculatingfatigue due to rotary bending, but with the adaptations required for when the weld issubjected to torsion. For this method, Wöhler's curve, Goodman and Gerber mean stresscorrection and Palmgren-Miner's rule have been used. The numerical method was performed in the commercial software FEMFAT, which hasbeen developed to calculate, among other things, fatigue and safety factors. This is asimulation program the company in question has, but previously not used for this purpose. During the process of developing these calculation methods, areas such as mean stresscorrection, fatigue strength and weld classi cation have been studied, and appropriatesettings for the simulation.This resulted in two calculation methods whose results differ greatly from each other.The analytical method is a very conservative method in which the fatigue damage that iscalculated becomes very high and according to the damage value the weld will fail. Forthe numerical method, on the other hand, the fatigue is very low and, according to thedamage value, will not fail. Based on this, it can be stated that the numerical method is the method considered mostreliable and should be further investigated and nally used. However, it is not possible togive a precis conclusion of whether the methods correspond to the reality, since no physicaltesting have been performed.